Investigation of the optimum calcination temperature for water treatment plant sludge to develop a sustainable alkali activated concrete - Jasmin Osama Abdelhalim; Ismail Amer; Ibrahim Abdel Latif; Ihab Fawzy; Sayed Ismail; Mohamed A. Khalaf (Scientific Reports, 2025)
Abstract Nowadays, Egypt is treating the Nile River Water to produce drinking water, and this process generates large amounts of waste, around 635 million m3 annually, which is called water treatment plant sludge (WTPS). This WTPS cost the government around 30 million US dollars to return it back to the Nile River in addition to negatively affecting the environment. Therefore, there is an urgent need to find environmentally friendly alternatives that reduce the impact of such an issue. This paper focuses on treating WTPS by drying, grinding and calcining to develop it as an alternative binder for use in alkali-activated concrete. This approach would not only provide green construction material but also reveal an environmental disposal route for the sludge produced in Egypt or in any country has the same issue. The treatment methodology used in this study was based on finding the optimum calcination temperature regime for WTPS after drying and grinding. Fifteen specimens of WTPS powder were used to investigate the optimum calcination temperature and duration by applying different temperatures ranging from 500 °C to 800 °C for various exposure durations of 30, 60 and 90 min. XRD and Chapelle tests were employed to chemically investigate the efficiency of the obtained calcined WTPS specimens, while strength activity index and compressive strength tests were used to mechanically verify the findings of the chemical tests. The results indicated that the calcination regime, which involved applying a maximum temperature of 650 °C for 90 min, achieved the best chemical characteristics and a strength activity index of 145%. Moreover, this regime resulted in a compressive strength of 21 MPa when WTPS powder was used as a precursor in alkali-activated concrete. Additionally, this paper presented a brief comparison of the production cost and energy consumption between cement and WTPS. The comparison demonstrated the efficiency of using WTPS as a replacement for cement, showing that the production of WTPS costs 50% less and consumes 92% less energy than cement.